Evaluating the mediating effect of behavioural and biological practices in the relationship between sociostructural risk factors and HIV infection outcomes among Adolescent Girls and Young Women: a cross-sectional study in central Uganda - Iddi Matovu; Rose Clarke Nanyonga; Christopher Ddamulira; and Miph Musoke. (BMC, 2025)
Background Adolescent Girls and Young Women (AGYW) face a heightened risk of new HIV Infections. However, research findings on the relationships between sociostructural risk factors, behavioural and biological practices, and HIV infection outcomes have been inconsistent. This study examines how behavioural and biological practices mediate the relationship between sociostructural risk factors and HIV infection outcomes among AGYW in Central Uganda. Methods We employed a quantitative, cross-sectional study to evaluate the mediating effect of behavioural and biological practices in the relationship between sociostructural risk factors and HIV Infection outcomes. Using simple random sampling, 375 AGYW participants aged 15–24 years with unknown HIV status were selected from Masaka Hospital Maternal Child Health Department (MCH) (253) and Out-Patient Department (OPD). Modeling (SEM) analyses were used to conduct mediation effect analyses using the Statistical Package for the Social Sciences (SPSS), version 27.0. Results Post-exposure prophylaxis (PEP) use (β=0.242, p=0.000) and the number of sexual partners (β=0.091, p=0.000) mediated the relationship between sociostructural risk factors such as alcohol consumption (β = -0.064, p=0.020), marital status (β = -0.086, p=0.001), exposure to sexual and gender-based violence (SGBV) (β=0.267, p=0.000), discrimination (β=0.070, p=0.031), and stigma (β=0.092, p=0.038) and HIV infection outcomes among AGYW in Central region. The most significant effect was observed in the pathway: SGBV→ PEP use →HIV infection contributing 6.5% of the total effects. There was a strong direct path from sociostructural risk factors to HIV infection with a factor load of 75.6%. In contrast, the indirect paths showed weaker effects: from sociostructural risk factors to biological practice with a factor load of 36.2%, and from biological practice to HIV infection with a factor load of 25.3%. Conclusion Limiting exposure to SGBV, addressing discrimination and HIV stigma, and encouraging the use of PEP should be a priority in reducing HIV infections among AGYW aged 15–24 years in Central Uganda. Keywords Adolescent girls, HIV infection, Risk factors, Uganda, Young women